Uji Organoleptik Teh Herbal Kulit Buah Naga (Hylocereus Polyrhizus) Kombinasi Jahe (Zingiber Officinale) sebagai Minuman Alternatif Tinggi Antioksidan - Meilan Cefinaayu Mayor; Yusvin Sampe; Jane Josina Antje Wambrauw; Riska Salenda Wandik; Endah Sri Rahayu; Ferry Wicaksono (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This study aimed to evaluate the organoleptic characteristics of herbal tea made from a combination of red dragon fruit peel (Hylocereus polyrhizus) with red ginger and white ginger. The herbal tea was formulated into six variants (F1a, F2a, F3a, F1b, F2b, F3b) based on different proportions of dragon fruit peel and tested using a hedonic method for three parameters: color, aroma, and taste. A total of 25 trained panelists assessed the level of preference using a 5-point hedonic scale. The results showed that Formula F3 (with the highest proportion of dragon fruit peel) received the highest acceptance scores. For color, F3 received an average of 19% in the “strongly like” category and 5% in the “like” category. For taste, F3 received 4% “strongly like” and 12% “like.” For aroma, F3 received 7% “strongly like” and 11% “like.” Thus, F3 was identified as the best organoleptic formula and is recommended for further development. This study suggests that additional research is needed to analyze the antioxidant activity of the product to better understand its functional health benefits.